Pseudo cardiac tamponade in the setting of excess pericardial fat - Zieroth Shelley; Raabe Michael; Walker Jonathan R; Francis Andrew; Kumar Kanwal; Nguyen Thang; Jassal Davinder S (Cardiovascular Ultrasound, 2009)
Abstract Cardiac tamponade is the phenomenon of hemodynamic compromise caused by a pericardial effusion. Following a myocardial infarction, the most common causes of pericardial fluid include early pericarditis, Dressler's syndrome, and hemopericardium secondary to a free wall rupture. On transthoracic echocardiography, pericardial fluid appears as an echo-free space in between the visceral and parietal layers of the pericardium. Pericardial fat has a similar appearance on echocardiography and it may be difficult to discern the two entities. We present a case of a post-MI patient demonstrating pseudo tamponade physiology in the setting of excessive pericardial fat.